STUDI KORELASI ANTARA PRESTASI BELAJAR BIDANG STUDI IPS DENGAN KESADARAN NASIONAL PADA SISWA KELAS VII MTs ALKHAIRAAT MADOPOLO KECAMATAN OBI UTARA - Asnita Ode Samili; Jainudin Hasim (Academy of Education Journal, 2021)
This research aims to determine the learning achievement of the Civics field of study with national awareness in Class VII students of MTs Alkhairaat Madopolo, North Obi District. Which aims to find out several things, namely, the level of learning achievement in the field of social studies and the level of national awareness in Class VII students of MTs Alkhairaat Madopolo, North Obi District and the relationship between the two The population in this study were all Class VII students of MTs Alkhairaat Madopolo, North Obi District in the school year. 2019/2020. The sampling technique is random sampling. Analysis of data for learning achievement in the field of social studies and national awareness used the arithmetic mean formula. Meanwhile, to analyze the correlation between social studies learning achievement with the level of national awareness, the correlation technique is the product moment correlation rough numbers. The results of the analysis of the existing data show that the average social studies achievement level is sufficient with an average value of 72.66. Analysis of the high national awareness variable with an average value of 92.44. Analysis of the correlation between learning achievement in the field of social studies with national awareness shows a significant relationship. With the learning achievement in the social studies field which is still in the adequate category, it needs to be improved by improving the teaching and learning process, especially in providing learning motivation for students. The level of national awareness of the students needs to be increased or at least maintained, especially in an atmosphere of the nation and state which is full of signs of disintegration. Social studies learning is only a part of the many lessons used to shape nationalistic attitudes in students to become good citizens.